2004
DOI: 10.1080/02841850410001079
|View full text |Cite
|
Sign up to set email alerts
|

Effect of contrast media on vascular smooth muscle cells

Abstract: Ionic IOT is more cytotoxic to VSMCs than non-ionic IOH. However, the cytotoxicity was minimal and similar between both CMs at 1 mmol/l Ca2+ in accordance with the sodium-calcium balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Thus, this concentration was used in the succeeding experiments. In previous studies, microbubbles exhibited side effects when injected into patients [21][22][23] . Our experiments demonstrated that the side effects of SonoVue microbubbles were not as evident as those of other reported ultrasound contrast media.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, this concentration was used in the succeeding experiments. In previous studies, microbubbles exhibited side effects when injected into patients [21][22][23] . Our experiments demonstrated that the side effects of SonoVue microbubbles were not as evident as those of other reported ultrasound contrast media.…”
Section: Resultsmentioning
confidence: 99%
“…CM normally induces dilation in healthy subjects [82,83], however, in CAD patients who typically exhibit endothelial dysfunction, coronary vasoconstriction or even vasospasm may occur [83,84]. In vitro studies have demonstrated that CM may exert negative effects on both EC [85,86] and VSMC [87,88]. CM is more likely to exert dose-dependent [89] vasoconstriction in segments close to a stenotic lesion [83,90], emphasizing a possible involvement of endothelial dysfunction, and constriction occurs more frequently following ionic CM than the currently used non-ionic CM [91].…”
Section: Does Contrast Media Using During Ptca/pci Cause Vascular Dysmentioning
confidence: 99%
“…Iohexol, a non-ionic contrast medium having low osmotic pressure, shows a high glomerulus filtration rate and is a safe contrast medium with little direct side effects on the tissue and cells, compared with other iodized contrast media, thus typically making it available for use in both humans and animals in clinical fields (Barkin et al, 1991). However, it is reported that iohexol with known safety is toxic for vascular endothelium cells (Takatsuki et al, 2004;Zhang et al, 2000) and renal cells (Duan et al, 2006;Gong et al, 2010;Lee et al, 2006). While numerous reports on the effects of iohexol on several types of cells are made available recently, research reports on its effects on chondrocytes are not to be found in the medical area as well as in the veterinary science.…”
Section: Introductionmentioning
confidence: 95%